Increase the Public Role of Labour Women Through Civic Education Training (Study in Cigarette Industry in Malang Municipality East Java Province) - Mardiyono, Haji Budhy Prianto (Advances in Social Sciences Research Journal, 2017)
Based on our previous research it was known that women workers were in weak position both personally and in the context of industrial relations. The weaknesses were caused by the lack of knowledge and understanding of: rights and obligations as workers, gender, and the rights and obligations as members of society and citizens. The research aimed to increase civic knowledge (cognitive) and understanding (affective) of labour women, especially related to politics. This research use qualitative experimental approach. The data were mainly obtained from interviews with labour women at post-civic education training. The results of the study show that, first, after training, there were little increase in knowledge and understanding about the politics of labour women. Second, qualitatively the improvement of knowledge and understanding was influenced by the quality of labour women’s education and the patriarchy culture shared by the family of labour women. Keywords: politics, women, labour, gender, civic education